Weight and volume measurement of fruit using PIC Microcontroller / Mohamad Nawawi Ab Rahman - Ab Rahman, Mohamad Nawawi (2009)
This technical paper presents a way to measure weight and volume using PIC Microcontroller. The project consists of two parts; first part measures weight and the second part to measure volume. A fruit electronic weight measuring device comprises a variable resistor as a device to produce voltage signals corresponding to the weight of load applied. Variable resistor converts weight to voltage as an input for PIC Microcontroller. For volume measurement part, infrared light photodetector circuit is use as a measurement device. Calculations of specific gravity fruit will be defined for ripeness after the measurement of weight and volume. The purpose of this paper is to present information on the feasibility of using specific gravity for measuring maturity of fruits(i.e.; tomatoes, citrus), and to show some relationships between volume and weight size (weight basis). In some fruits and vegetables changes in density and composition have been correlated with specific gravity. Relationship between fruit size and specific gravity has been reported. In studies of fruit size, smaller oranges [and grapefruit had higher solids than the larger fruits, but the reverse was true for apples [1]. The specific gravity is given by the {S.G = Density of fruit (g/cm3 )/ Density of water (g/cm3 )} density of the material divided by the density of water at the same temperature. The specific gravity will generally increase with fruit maturity [2].